Investigating the Efficacy of Early Intervention Strategies in Preventing Joint Damage in High Risk Rheumatoid Arthritis Patients - Aslam, Sharmeen; Iqbal , Mubasshra; Shaheryar, Muhammad; Arslan , Muhammad (Indus Journal of Bioscience Research, 2025)
Objectives: To evaluate the clinical and radiographic efficacy of early DMARD initiation in preventing joint damage among high-risk RA patients. Study Settings: Rheumatology Department, tertiary care hospital. Duration of Study: 12 months. Data Collection: This prospective randomized controlled trial included 256 patients with newly diagnosed high-risk RA, stratified into Early (DMARDs within 6 weeks of symptom onset) and Delayed (DMARDs after 6 months) intervention groups. Patients were assessed using DAS28, HAQ-DI, and Sharp/van der Heijde scores over 12 months. ACR20 response and radiographic progression were primary outcomes. Results:The Early group showed significantly greater clinical improvement and joint preservation. ACR20 was achieved in 55.5% of the Early group vs. 28.1% in the Delayed group (p = 0.0000). Mean reduction in DAS28 score was greater in the Early group (from 5.58 to 3.56) than in the Delayed group (to 4.57; p = 0.0000). Radiographic progression was significantly lower in the Early group, with a Sharp score increase of 0.49 vs. 2.69 in the Delayed group (p = 0.0000). Conclusion: Early intervention with DMARDs significantly improves clinical outcomes and prevents joint damage in high-risk RA patients.